Kualitas Fisik Pellet dengan Penambahan Level Tepung Daun Ubi Kayu serta Bahan Perekat yang Berbeda - Anwar Efendi Harahap; Wieda Nurwidada Haritsah Zain (Wahana Peternakan, 2021)
ABSTRACT One alternative that can be used for poultry feed is cassava flour (Manihot esculenta) which can be made into pellets. The purpose of this research was to know the physical quality of water content (KA), specific gravity (BJ), stack angle (ST), stack density (KT), stack compaction density (KPT), and impact resistance (KB) of pellet product with utilization of flour cassava (Manihot esculenta). This research using Completely Randomized Design (RAL) Factorial. Factor A consisting of 3 treatments, that were A0: without adding cassava leaf flour, A1: 5% andÂ  A2: 10% in ration formulation and Factor B consisting of 3 treatments binders, that were B0 : basal ration not binders,Â  B1: tapioca starch and B2: wheat flour. The results showed that the interaction between the addition of cassava leaf flour and binders with different levels can be seen from water content, stack angle and stack compaction density, but on specific gravity, stack density and impact resistance did not occur interaction. It can be concluded that the addition of 10% cassava flour with tapioca flour binders gives the best quality of pellet physical properties to moisture content and stack angle, while other treatment combinations have not been able to improve pellet quality based on specific gravity, stack density, stack compaction density and impact resistance. Keywords: Pellet, Cassava Leaf, Flour, Binders